A STUDY OF MATHAYOMSUKSA III STUDENTS’ PROOF ABILITIES IN GEOMETRY THROUGH A LEARNING MANAGEMENT WITH INQUIRY-BASED METHOD FOR CIRCLE TOPICS - เพ็งเจริญ เสฎฐวุฒิ; ศรีภิรมย์ สิรินิลกุล พิศุทธวรรณ; จันทรจรูญ เอนก (Journal of Industrial Education, 2018)
The purpose of this study was to study students’ proof abilities in geometry before and after learning circle topics following a designed learning management with a method of inquiry-based learning. This study was an experimental research conducted during the second semester of the 2017 academic year. Forty-four Mathayomsuksa III students from Debsirin School in Bangkok, Thailand, were recruited to be participants via a method of cluster random sampling. A pretest on proof abilities in geometry was taken at the beginning as part of the pretest-posttest design. The students then learned the subjects according to the lesson plans in the learning management in which provided students to engage in inquiry-based learning. A parallel-structure posttest was given at the end of the lesson plans. The dependent t-test was employed in the analysis of data. The findings reveal that the students gained significantly in terms of proof abilities in geometry from learning through the lesson plans with inquiry-based learning at the .01 level.